Theory-practice, a Nonfunctional Tandem in Romanian Technical Higher Education. (2015) - Banciu, Felicia Veronica; Pămîntaş, Eugen
Abstract: From education psychology point of view, practice is any independent achievement the trainees made at the proposal and under the guidance of school, progressing to assume increasing autonomy and personal responsibility. On a declarative level, education providers around the world claim that the practice is the essential link between specialists' trainer and the knowledge society needs. This paper's aim is to analyze the technical professional practice deployed in Romania regarding the three main actors involved in educational process - employers, students and universities and its result is an argumentation whether there is or not a need to change in the way the professional practice is done/seen by employers and universities.